The effect of auditor rotation, time pressure, and audit tenure on audit quality with auditor specialization as moderation variable: (empirical study of manufacturing companies listed on the Indonesia stock exchange in 2014-2018) - Kirana, I Gusti Ayu Monika Intan; Ramantha, I Wayan (International research journal of management, IT and social sciences, 2020)
The purpose of this study was to determine and obtain empirical evidence about the effect of auditor rotation, time pressure, and audit tenure on audit quality with auditor specialization as a moderating variable. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The number of samples is 81 companies with the number of observations as many as 405 samples in 5 years, through the nonprobability method with a purposive sampling technique. This research analysis technique uses Moderate Regression Analysis (MRA). Based on the results of the analysis found that audit rotation does not affect audit quality. Time pressure influences audit quality. Audit tenure affects audit quality. The auditor's specialization does not affect audit quality.